Leveling the playing field: evaluating measurement equivalence in MMIs between genders - Szkwara, Jaclyn Michele; Bannatyne, Amy Jean; Asil, Mustafa; Craig, Belinda; Stokes-Parish, Jessica; Bishop, Jo (Frontiers in Medicine, 2025)
IntroductionThe selection process for medical schools plays a vital role in identifying candidates with the attributes and capabilities needed for success in medicine. Multiple Mini-Interviews (MMI) are widely used to assess non-cognitive attributes like communication, empathy, and ethical judgment. Ensuring their fairness and validity across diverse applicant groups is essential for equitable selection.AimsThis study aimed to investigate: (1) is there evidence to support the factorial validity of MMI structure; (2) whether non-cognitive attributes assessed by MMIs are consistently interpreted across gender groups; and (3) whether gender-related disparities exist in MMI performance.MethodsData were drawn from applicants to an Australian Medical School across three selection cycles (2022–2024). Confirmatory Factor Analysis (CFA) was used to assess the dimensionality of MMI performance, with multiple competing models tested to identify the best-fitting structure. The selected model was then assessed for measurement invariance across gender using Multi-Group CFA. Once scalar invariance was established, latent mean comparisons were conducted to examine gender-related differences in MMI performance.ResultsCFA indicated a well-fitting structure for MMIs, with a higher-order model emerging as the most appropriate representation across cohorts. Measurement invariance testing confirmed scalar invariance across gender groups, indicating that MMI non-cognitive attributes were demonstrated equivalently by males and females. Significant latent mean differences were identified, with female applicants consistently outperforming male applicants across all 3 years.DiscussionThe results provided empirical support for the factorial validity and measurement fairness of the MMI across gender groups. However, the consistent gender-based performance differences highlight the need for continued research into potential sources of group disparities and how they may impact selections equity. The results are relevant for medical educators and policymakers committed to evidence-based and equitable selection processes.